2019
DOI: 10.1039/c8dt03211d
|View full text |Cite
|
Sign up to set email alerts
|

A selective hydrolytic and restructuring approach through a Schiff base design on a coumarin platform for “turn-on” fluorogenic sensing of Zn2+

Abstract: The designed molecular probe, CMD, undergoes Zn2+ triggered restructuring and shows a fluorescence change in only 30 seconds. The LOD was found to be of sub-nanomolar level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Nevertheless, the use of imines in biological research is associated with the possibility of hydrolysis of these compounds [24]. However, the imines described in the literature, which underwent hydrolysis and had a significant impact on the properties, most often contained a unit with an imine bond in their structures, capable of complexing ions [25][26][27][28][29][30][31][32]. It should be noted that earlier studies have shown that, despite partial hydrolysis of the compounds, biological activity was associated with the presence of non-hydrolyzed imine [26].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of imines in biological research is associated with the possibility of hydrolysis of these compounds [24]. However, the imines described in the literature, which underwent hydrolysis and had a significant impact on the properties, most often contained a unit with an imine bond in their structures, capable of complexing ions [25][26][27][28][29][30][31][32]. It should be noted that earlier studies have shown that, despite partial hydrolysis of the compounds, biological activity was associated with the presence of non-hydrolyzed imine [26].…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding plot of fluorescence intensity versus the concentration of Zn 2+ was constructed and a good linear relationship was observed over the range of 2∼15 μM (Figure S4). Based on the rule of 3σ/slope, the detection limit of HL to Zn 2+ in THF/H 2 O (3:7, v/v) was estimated to be 1.07 × 10 –7 M. The UV–vis absorption spectra of HL at variable concentrations in THF/H 2 O (3:7, v/v) were also measured and are presented in Figure S5a. There are two peaks centered at 265 and 316 nm corresponding to π–π* and n –π* transitions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Peaks were detailed on BRUKER 300 MHz instrument by using CDCl3 as solvent. One singlet peak was observed for CH3 group, one broad peak at δ 5.025 ppm shows residual NH2, aromatic benzene ring protons were shown in the form of multiplet at δ 7.562-6.743 ppm, one more deshielded singlet was recorded at δ 8.404 ppm for (-CH=N-) proton, one singlet was observed at δ 9.890 ppm for OH group [33,34].…”
Section: H-nmrmentioning
confidence: 98%